'Insubordinate Irish' : Travellers in the text - Ó hAodha, Mícheál, 1969- (Book collections on Project MUSE., 2011)
This book traces a number of common themes relating to the representation of Irish Travelers in Irish popular tradition and how these themes have impacted on Ireland's collective imagination. A particular focus of the book is on the exploration of the Traveler as "Other," an "Other" who is perceived as both inside and outside Ireland's collective ideation. Frequently constructed as a group whose cultural tenets are in a dichotomous opposition to that of the "settled" community, this book demonstrates the ambivalence and complexity of the Irish Traveler "Other" in the context of a European postcolonial country. Not only has the construction and representation of Travelers always been less stable and "fixed" than previously supposed, these images have been acted upon and changed by both the Traveler and non-Traveler communities as the situation has demanded. Drawing primarily on little-explored Irish language sources, this volume demonstrates the fluidity of what is often assumed as reified or "fixed." As evidenced in Irish-language cultural sources the image of the Traveler is inextricably linked with the very concept of Irish identity itself. They are simultaneously the same and "Other" and frequently function as exemplars of the hegemony of native Irish culture as set against colonial traditions. This book is an important addition to the Irish Studies canon, in particular as relating to those exciting and unexplored terrains hitherto deemed "marginal" - Traveler Studies, Romani Studies, and Diaspora/Migration Studies to name but a few.